Developing explicit and implicit L2 knowledge with Duolingo’s input-based features: Case studies of L2 Spanish learning - Brandy, Anthony; Hiver, Phil (Studies in Second Language Learning and Teaching, 2024)
In this single-case study with a quasi-experimental design, we set out to examine the role of two input-based features of the language learning app Duolingo on learners’ development of implicit and explicit second language (L2) knowledge. We investigated the effect of Duolingo’s Stories feature and Podcast feature on two Spanish-L2 learners’ performance on a battery of implicit and explicit L2 knowledge tests. Once a week, over a four-week period using these input-based features, both participants repeatedly performed oral narrative tasks, timed and untimed grammaticality judgment tasks, and metalinguistic knowledge tests. The participant assigned to the Podcast condition showed meager gains in productive implicit knowledge (measured by oral narrative tasks) but decreased in receptive explicit knowledge (measured by untimed grammaticality judgment tasks). The participant assigned to the Stories condition showed a large increase in receptive implicit knowledge of Spanish (measured by timed grammaticality judgment tasks). Neither participant showed meaningful gains in the measure of productive explicit knowledge (measured by metalinguistic knowledge tasks). Although there was a slight increase in receptive explicit knowledge for the participant using Stories, the data from both participants discount the idea that app-based mobile-assisted language learning (MALL) prioritizes receptive explicit L2 knowledge, at least when considering these novel input-based features of Duolingo. These findings add nuance to previous research showing that the primary outcome of MALL app use is receptive explicit L2 knowledge.